Characterization of a novel IGFBP-2 transcript in the ovarian granulosa cells of chicken follicles: mRNA expression, function and effect of reproductive hormones and IGF1 - Longxiao Hu; Dandan Li; Qingqing Wei; Li Kang; Yi Sun; Yunliang Jiang (Poultry Science)
Insulin-like growth factor binding protein-2 (IGFBP-2), a binding protein of insulin-like growth factor (IGF) system, regulates the activity of IGFs and also influences cellular function with endogenous activity. In mammals, IGFBP-2 is reported to affect ovarian follicle development and steroidogenesis; however, its role in the chicken ovary is unknown. In this study, we investigated the mRNA expression and function of a novel IGFBP-2 transcript and the effect of reproductive hormones and insulin-like growth factor 1 (IGF1) on its expression in the ovarian granulosa cells of chicken follicles. The mRNA expression of IGFBP-2 was significantly increased in granulosa cells after follicle selection and was higher in hierarchical granulosa cells (Post-GCs) than in pre-hierarchical granulosa cells (Pre-GCs). IGFBP-2 promoted the proliferation and inhibited the apoptosis of both Pre-GCs and Post-GCs, enhanced the mRNA expression of genes involved in progesterone (P4) synthesis in Pre-GCs. However, in Post-GCs, IGFBP-2 inhibited the mRNA expression of these genes and suppressed P4 secretion. The mRNA expression of IGFBP-2 was inhibited by estradiol (E2) and follicle-stimulating hormone (FSH), but enhanced by P4 in Pre-GCs. In Post-GCs, FSH and IGF1 stimulated the mRNA expression of IGFBP-2 synergistically. Knockdown of IGFBP-2 attenuated the stimulatory effect of IGF1 on the mRNA expression of the side chain cleavage enzyme cytochrome P450 family 11 subfamily A member 1 (CYP11A1). These findings indicate that IGFBP-2 is regulated by FSH and IGF1, exerts different functions in Pre-GCs and Post-GCs in regulating IGF1 and plays an important role in chicken follicle development by affecting granulosa cell proliferation and P4 synthesis.